Matrix Sequences in terms of Padovan and Perrin Numbers - Nazmiye Yilmaz; Necati Taskara (Journal of Applied Mathematics)
The first main idea of this paper is to develop the matrix sequences that represent Padovan and Perrin numbers. Then, by taking into account matrix properties of these new matrix sequences, some behaviours of Padovan and Perrin numbers will be investigated. Moreover, some important relationships between Padovan and Perrin matrix sequences will be presented.